Eye-colour changes in flightless ducklings of Lesser and Greater Scaup Aythya affinis and A. marila - Nelson, C H (Wildfowl, 1996)
Both Scaup species have eye-colour that is some shade of olive at hatching, both have some shade of yellow as adults, and both show little change in chroma of eye-colour but an increase in value. However, there is a marked change in the hue of eye-colour between Lesser and Greater Scaup at the late downy stage. Ducklings can be distinguished at this late downy stage by eye-colour; blue-eyed birds are all Greater Scaup, while the eyes of young Lesser Scaup always have a yellow element.